2020
DOI: 10.3389/fonc.2020.01595
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TIGIT in NK and T Cells Contributes to Tumor Immune Escape in Myelodysplastic Syndromes

Abstract: Targeting immune checkpoints, such as PD-1, represents a promising approach for cancer immunotherapy, achieving long-term disease remission rates in numerous types of cancer. T cell immunoglobulin and ITIM domain (TIGIT) is a checkpoint receptor associated with the antitumor roles of NK and T cells. Notably, the blockade of TIGIT has been revealed as a potential promising approach in cancer immunotherapy. However, the therapeutic potential of blocking TIGIT in myelodysplastic syndrome (MDS) remains unclear and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 39 publications
(42 reference statements)
1
37
0
Order By: Relevance
“…Stanietsky et al have shown that TIGIT can inhibit NK cells cytotoxicity, and its blockade can upregulate interferon-γ (IFN-γ) [ 32 ]. Meng et al have reported that TIGIT + NK cells express fewer IFN-γ and tumor necrosis factor-α (TNF-α) than TIGIT-NK cells, and the high expression of TIGIT is associated with decreased function of NK cells and immune evasion of tumoral cells [ 33 ]. Moreover, TIGIT has been implicated in impairing the anti-tumoral immune responses of CD8 + T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Stanietsky et al have shown that TIGIT can inhibit NK cells cytotoxicity, and its blockade can upregulate interferon-γ (IFN-γ) [ 32 ]. Meng et al have reported that TIGIT + NK cells express fewer IFN-γ and tumor necrosis factor-α (TNF-α) than TIGIT-NK cells, and the high expression of TIGIT is associated with decreased function of NK cells and immune evasion of tumoral cells [ 33 ]. Moreover, TIGIT has been implicated in impairing the anti-tumoral immune responses of CD8 + T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Reports about the TIGIT expression on NK-cells in patients with malignant diseases are indecisive. Increased expression of TIGIT on NK-cells in the peripheral blood has been reported in patients with myelodysplastic syndrome ( 230 ), high risk non-muscle invasive bladder cancer ( 231 ) and gastrointestinal cancer (gastric and colon cancer) ( 171 ). Patients with colon cancer show higher TIGIT expression on NK-cells in intratumoral regions than in peritumoral regions ( 232 ).…”
Section: Pathologymentioning
confidence: 99%
“…T-cell immunoreceptor with Ig and ITIM domains (TIGIT) is a novel coinhibitory receptor expressed by T and NK cells that binds to CD155, leading to impaired T or NK cell anti-tumorigenic functions ( 98 ). TIGIT is an emerging target in cancer immunotherapy where its activation in T cells by its ligand CD155 or CD112 expressed by cancer cells inhibits T cell responses ( 99 ).…”
Section: Activation Of Antileukemic T Cellsmentioning
confidence: 99%